OsMADS1 Represses microRNA172 in Elongation of Palea/Lemma Development in Rice - Dai, Zhengyan; Wang, Jiang; Zhu, Mulan; Miao, Xuexia; Shi, Zhenying (Frontiers in Plant Science, 2016)
Specification of floral organ identity is critical for the establishment of floral morphology and inflorescence architecture. Although multiple genes are involved in the regulation of floral organogenesis, our understanding of the underlying regulating network is still fragmentary. MADs-box genes are principle members in the ABC model that characterized floral organs. OsMADS1 specifies the determinacy of spikelet meristem and lemma/palea identity in rice. However, the pathway through which OsMADS1 regulates floral organs remains elusive; here, we identified the miR172 family as possible regulators downstream of OsMADS1. Genetic study revealed that overexpression of each miR172 gene resulted in elongated lemma/palea and indeterminacy of the floret, which resemble the phenotype of osmads1 mutant. On the contrary, overexpression of each target APETALA2 (AP2) genes resulted in shortened palea/lemma. Expression level and specificity of miR172 was greatly influenced by OsMADS1, as revealed by Northern blot analysis and In situ hybridization. Genetically, AP2-3 and AP2-2 over expression complemented the elongation and inconsistent development of the lemma/palea in OsMADS1RNAi transgenic plants. Our results suggested that in rice, OsMADS1 and miR172s/AP2s formed a regulatory network involved in floral organ development, particularly the elongation of the lemma and the palea.